(untitled) (Italiano LinguaDue, 2023)
Over the past decade, Malta has seen a steady increase in the amount of Italian nationals who work, study and reside on the island. This is a significant recent development in the contacts between Malta and Italy and represents another important milestone in the relationships between the two countries, rooted in language, history and culture. Today, Italians are practically present in every sector of Maltese society and their move to the island is mainly determined by employment opportunities in an Anglophone context which is geographically close to their homeland. Research on this migration has been carried out over the past years in order to investigate language issues, schooling and socialisation. In this paper I provide an overview of the main results obtained in these studies, while also reflecting on how they are relevant for future research on Italians in Malta. Una rassegna della ricerca sulla recente migrazione degli italiani a Malta Durante l’ultimo decennio, a Malta si è registrato un aumento considerevole di Italiani che lavorano, studiano e risiedono sull’isola. Si tratta di uno sviluppo significativo dei contatti tra Malta e l’Italia e rappresenta un’altra tappa fondamentale nelle relazioni tra i due Paesi, le quali hanno radici linguistiche, storiche e culturali. Oggi gli Italiani sono presenti in praticamente tutti i settori della società maltese e, nella maggior parte dei casi, il loro trasferimento è determinato da opportunità lavorative in un contesto anglofono vicino al loro Paese. Argomenti linguistici, la scuola e la socializzazione sono tra i temi che sono stati investigati nelle ricerche svolte recentemente in merito a questa migrazione. In questo lavoro si propone una rassegna dei risultati principali e si riflette sulla rilevanza di queste conclusioni per studi futuri sugli Italiani a Malta.